2020
DOI: 10.1021/acs.jafc.9b08107
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Phytoestrogen Metabolites in Breastfed Infants’ Urine and the Corresponding Breast Milk by Liquid Chromatography–Tandem Mass Spectrometry

Abstract: To date, there has been limited information on phytoestrogen (PE) exposure and metabolism in breastfed infants. In the present work, 50 sample pairs of Chinese breastfed infants’ urine and the corresponding breast milk were collected. The contents of the relevant PE metabolites in the biosamples were detected via liquid chromatography–tandem mass spectrometry. The correlations between the PE metabolite contents in breastfed infants’ urine and those in the corresponding breast milk were analyzed. The average co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…In contrast to the study by Franke and Custer (1996), Zhou et al (2020) found that after a Chinese woman consumed 500 ml soymilk, maximum isoflavone breastmilk concentrations were reached much earlier, after only six h. At this time point, mean genistein and daidzein concentrations were approximately 99 (270 nM) and 104 ug/kg (260 nM), respectively. These concentrations are similar to those reported by Min, Wang, and Liang (2020) for Chinese women, as genistein and daidzein concentrations in breastmilk were 144 nmol/l (38.92 ug/l) and 52 nmol/l (13.09 ug/l), respectively. The urinary genistein and daidzein concentrations of the breastfed infants were 96 nmol/l and 44 nmol/l, respectively.…”
Section: Breastfeedingsupporting
confidence: 89%
“…In contrast to the study by Franke and Custer (1996), Zhou et al (2020) found that after a Chinese woman consumed 500 ml soymilk, maximum isoflavone breastmilk concentrations were reached much earlier, after only six h. At this time point, mean genistein and daidzein concentrations were approximately 99 (270 nM) and 104 ug/kg (260 nM), respectively. These concentrations are similar to those reported by Min, Wang, and Liang (2020) for Chinese women, as genistein and daidzein concentrations in breastmilk were 144 nmol/l (38.92 ug/l) and 52 nmol/l (13.09 ug/l), respectively. The urinary genistein and daidzein concentrations of the breastfed infants were 96 nmol/l and 44 nmol/l, respectively.…”
Section: Breastfeedingsupporting
confidence: 89%
“…Fruit (oranges, mandarins and orange juice) contributed tõ 26% of (poly)phenols intake in the MTC, followed by cereals and tubercules with 10% and vegetables and legumes with 9% [52]. Serum and urinary levels of equol were higher compared to Asian infants (11.36 ng/mL urine) [20] and adults (<0.54-0.63 ng/mL urine) [41], and adults supplemented with isoflavones (not detected plasma levels after 123 mg soy supplementation) [53].…”
Section: Analysis Of Phytoestrogens In Food Serum and Urinementioning
confidence: 98%
“…Gas chromatography-mass spectrometry (GC-MS) is a technique with high sensitivity and selectivity but requires several clean-up steps, complex sample preparation and derivatization [14,16,17]. LC-MS is the analytical method preferred due to a simple sample preparation, high sensitivity and specificity [18][19][20]. Recently, advances on LC separation along with MS n structural information and resolving power have improved identification and quantification of small molecules in complex matrices in the lower ppb-level.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to remove milk protein and fat content before analysis, as previously suggested . Most previous studies have determined polyphenols in human milk after enzymatic hydrolysis and subsequent extraction with ethyl acetate or diethyl ether. ,,, Protein precipitation with ACN has also been used in previous works to quantify total phenolic compounds in breast milk using the Folin–Ciocalteu method and isoflavones after enzymatic hydrolysis . However, in these cases, relevant information about the naturally occurring metabolites is missing.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of dietary phenolics in breast milk, their metabolizing bacteria, and the metabolites produced has still been less explored. There are only a few studies, and most of them focused on isoflavones and other flavonoid metabolites. Little is known about the existence of urolithins or urolithin-producing bacteria in breast milk. Only the presence of glucuronide conjugates of Uro-A and Uro-B has been reported in human breast milk , from only two and one volunteer, respectively.…”
Section: Introductionmentioning
confidence: 99%